THE SOCIAL RESPONSIBILITY OF THE CHEMISTRY TEACHER - Daniels, D. J. (SCHOOL SCIENCE, 2012)
The last two decades have seen the development worldwide of many new chemistry curricula for the secondary level, nearly all of which have been characterised by an increased academic—and even esoteric—content. The same period has witnessed a relative decrease in students, especially the more able ones, taking chemistry degrees in many countries. It is my contention that this is an example of cause and effect and that to motivate more able students to consider courses and careers in chemistry, it is necessary at the secondary level that chemistry should be seen to have relevance to the students.